The Nazi Germany sourcebook : an anthology of texts - Stackelberg, Roderick; Winkle, Sally Anne (Routledge, 2002)
The Nazi Germany Sourcebook is an exciting new collection of documents on the origins, rise, course and consequences of National Socialism, the Third Reich, the Second World War, and the Holocaust.